Salt-excluder rootstock improves physio-biochemical responses of grafted grapevine plants subjected to salinity stress - Elania Freire da Silva; Hugo Rafael Bentzen Santos; Jean Pierre Henry Balbaud Ometto; Alexandre Maniçoba da Rosa Ferraz Jardim; Thieres George Freire da Silva; Pedro José Hermínio; Adriano Nascimento Simões; Eduardo Souza; Sérgio Luiz Ferreira-Silva (Current Plant Biology, 2024)
This study tests the hypothesis that a more salt-excluder rootstock can attenuate salt stress in grapevine plants by enhancing photosynthesis and providing ionic and oxidative protection. Plants of ‘BRS Vitória’ variety, grafted with the rootstocks IAC 313 (salt-excluder) and SO4, were subjected to salinity by adding NaCl (0, 50, and 100 mM) for 30 days. Plants with SO4 showed more severe salt toxicity symptoms in leaves and lower chlorophyll content under salinity. Conversely, plants with IAC 313 showed improved photosynthesis and stomatal conductance, along with higher carboxylation efficiency under salt compared to SO4. Under salinity, plants with SO4 showed higher losses of K+ in stems, roots, and petioles, as well as increased accumulation of Na+ in these organs, relative to IAC 313. Furthermore, plants with IAC 313 had lower leaf Na+ content under salinity and reduced leaf Cl− content at 50 mM NaCl, a response associated with a higher Na+ allocation in petioles of IAC 313. At 50 mM, IAC 313 exhibited better photochemical activity, as indicated by electron transport rate and non-photochemical quenching. However, at 100 mM, both rootstocks showed similar trends, suggesting that the photosynthetic restriction was primarily due to stomatal disturbances. Plants with IAC 313 showed better APX activity and ascorbate balance under salinity. IAC 313 showed more salt-resistance traits than SO4, although the growth was similarly affected in both rootstocks. This response could be due to the reduced time of salt treatment (30 days). In summary, our data indicate that IAC 313 rootstock possesses better salt tolerance traits than SO4.